Determination of the Optimal Programmed Intermittent Epidural Bolus Volume of Bupivacaine 0.0625% With Fentanyl 2 μg/mL at a Fixed Interval of 40 Minutes: A Biased Coin Up-and-down Sequential Allocation Trial. Issue 1 (March 2019) - Zakus, P.; Arzola, C.; Bittencourt, R.; Downey, K.; Ye, X.Y.; Carvalho, J.C.
Abstract : ( Anaesthesia . 2018;73:459–465) The use of programmed intermittent epidural bolus (PIEB) to provide labor analgesia has been increasing in popularity as commercially available pumps have become available. A variety of dosing strategies have been evaluated but the optimal settings for PIEB have not yet been established. The majority of studies have included PIEB in conjunction with patient controlled epidural analgesia (PCEA). The current investigators had previously investigated which PIEB dosing strategy would minimize breakthrough pain and the need for PCEA boluses. They determined the optimal regimen was 10 mL of bupivacaine 0.0625% with fentanyl 2 µg/ml administered every 40 minutes. However, 34% of women exhibited a sensory block to ice above T6, which might indicate an unnecessarily high spread of local anesthetic. Therefore, they conducted this prospective, double-blind, dose-finding study to investigate whether it was possible to reduce the PIEB volume without compromising the efficacy of the technique.